Dapagliflozin‐induced weight loss affects 24‐week glycated haemoglobin and blood pressure levels. Issue 8 (27th June 2015) - Sjöström, C. D.; Hashemi, M.; Sugg, J.; Ptaszynska, A.; Johnsson, E.
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the associations between dapagliflozin‐mediated reductions in body weight and reductions in glycated haemoglobin (HbA1c) and blood pressure. Data were pooled from seven studies evaluating dapagliflozin 10 mg as monotherapy or combination therapy over 24 weeks. Using linear regression to estimate the contribution of weight loss to HbA1c and blood pressure reductions, the β‐value estimate for HbA1c (%)/kg was 0.028 (p < 0.0001). Weight loss of 2 kg with dapagliflozin contributed to 6% of the total HbA1c reduction. For systolic (SBP) and diastolic blood pressure (DBP), the β‐value (mmHg/kg) estimates were 0.606 (p < 0.0001) and 0.253 (p < 0.0001), respectively. Weight loss of 2 kg contributed to 28% of the overall SBP reduction, and 24% of the overall DBP reduction. In conclusion, dapagliflozin‐mediated weight loss may contribute to overall reductions in HbA1c and blood pressure.